Long-term reproducibility of optical coherence tomography angiography in healthy and stable glaucomatous eyes - Nishida, Takashi; Moghimi, Sasan; Hou, Huiyuan; Proudfoot, James A; Chang, Aimee C; David, Ryan Caezar C; Kamalipour, Alireza; El-Nimri, Nevin; Rezapour, Jasmin; Bowd, Christopher; Zangwill, Linda M; Weinreb, Robert N (British journal of ophthalmology, 2023)
Background/aimsTo assess and compare long-term reproducibility of optic nerve head (ONH) and macula optical coherence tomography angiography (OCTA) vascular parameters and optical coherence tomography (OCT) thickness parameters in stable primary open-angle glaucoma (POAG), glaucoma suspect and healthy eyes.MethodsEighty-eight eyes (15 healthy, 38 glaucoma suspect and 35 non-progressing POAG) of 68 subjects who had at least three visits within 1–1.5 years with OCTA and OCT imaging (Angiovue; Optovue, Fremont, California, USA) on the same day were included. A series of vascular and thickness parameters were measured including macular parafoveal vessel density (pfVD), ONH circumpapillary capillary density (cpCD), macular parafoveal ganglion cell complex (pfGCC) and ONH circumpapillary retinal nerve fibre layer (cpRNFL). A random effects analysis of variance model was used to estimate intraclass correlation (ICC) coefficients and long-term variability estimates.ResultsICC was lower for OCTA (pfVD 0.823 (95% CI 0.736 to 0.888) and cpCD 0.871 (0.818 to 0.912)) compared with OCT (pfGCC 0.995 (0.993 to 0.997) and cpRNFL 0.975 (0.964 to 0.984)). Within-subject test–retest SD was 1.17% and 1.22% for pfVD and cpCD, and 0.57 and 1.22 µm for pfGCC and cpRNFL. Older age and lower signal strength index were associated with decreasing long-term variability of vessel densities.ConclusionsOCTA-measured macula and ONH vascular parameters have good long-term reproducibility, supporting the use of this instrument for longitudinal analysis. OCTA long-term reproducibility is less than OCT-measured thickness reproducibility. This needs to be taken into consideration when serial OCTA images are evaluated for change.Trial registration number NCT00221897.